Insulin analogues in children with Type 1 diabetes: a 52-week randomized clinical trial - BEREKET, ABDULLAH (WILEY, 2013)
Aims This 52-week, randomized, multinational, open-label, parallel-group, non-inferiority trial investigated the efficacy and safety of basalbolus treatment with insulin detemir vs. NPH (neutral protamine Hagedorn) insulin, in combination with insulin aspart, in subjects aged 216 years with Type 1 diabetes mellitus. Methods Of the 347 randomized and exposed subjects, 177 received insulin detemir and 170 NPH insulin, both administered once or twice daily in combination with mealtime insulin aspart. Glycaemic measurements and weight were followed over 52 weeks. Results After 52 weeks, insulin detemir was shown to be non-inferior to NPH insulin with regard to HbA1c [mean difference insulin detemirNPH: 1.30 mmol/mol, 95% CI 1.32 to 3.92 (0.12%, 95% CI 0.12 to 0.36) in the full analysis set and 1.41 mmol/mol, 95% CI 1.26 to 4.08 (0.13%, 95% CI 0.12 to 0.37) in the per protocol analysis set]. Hypoglycaemic events per subject-year of exposure of 24-h and nocturnal hypoglycaemia were significantly lower with insulin detemir than with NPH insulin (rate ratio 0.76, 95% CI 0.600.97, P = 0.028 and 0.62, 95% CI 0.470.84, P = 0.002, respectively). Weight standard deviation (sd) scores (body weight standardized by age and gender) decreased with insulin detemir, but increased slightly with NPH insulin (change: 0.12 vs. 0.04, P < 0.001). At end of the trial, median insulin doses were similar in both treatment groups. Conclusions Insulin detemir was non-inferior to NPH insulin after 52 weeks' treatment of children and adolescents aged 216 years, and was associated with a significantly lower risk of hypoglycaemia, together with significantly lower weight sd score when compared with NPH insulin. Diabet. Med. 30, 216-225 (2013)
Keywords: BLOOD-GLUCOSE CONTROL; NEUTRAL PROTAMINE HAGEDORN; BASAL-BOLUS REGIMEN; NPH INSULIN; MICROVASCULAR COMPLICATIONS; GLYCEMIC CONTROL; DETEMIR; HYPOGLYCEMIA; THERAPY; PEOPLE